2005
DOI: 10.1021/jp046498z
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Energetic, and Spectroscopic Features of Lower Energy Complexes of Superoxide Hydrates O2-(H2O)1-4

Abstract: The lower-energy portions of the potential energy surfaces of superoxide hydrates O2(-)(H2O)(1< or = n < or = 4) are thoroughly investigated at high computational levels. The structural, energetic and spectroscopic features of the stable superoxide hydrates on these potential energy surfaces are discussed, focusing in particular on some implications to their infrared spectra and the hydrogen bond trends. The present work reports the transition-state linkers between the most stable superoxide hydrates which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…− (H 2 O) m , 10,12,13 supported by theoretical studies, 14,15 showed that all species with n ≥ 2 form an O 4 − core anion. The relatively high binding energy of O 2 to O 2 − (0.455 ± 0.22 eV) (Ref.…”
Section: Introductionmentioning
confidence: 79%
“…− (H 2 O) m , 10,12,13 supported by theoretical studies, 14,15 showed that all species with n ≥ 2 form an O 4 − core anion. The relatively high binding energy of O 2 to O 2 − (0.455 ± 0.22 eV) (Ref.…”
Section: Introductionmentioning
confidence: 79%
“…A number of theoretical works have investigated the properties of solvated superoxide. A number of these studies focusing on the O 2 − ͑H 2 O͒ m clusters 25,26 have indicated that water forms a single hydrogen bond with the O 2 − core, leaving a free O-H group, which tends to form hydrogen bonds with adjacent water molecules in the larger hydrates. This structural motif has been confirmed by gas-phase infrared spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…20 For comparison, the O 2 − · · HOH bond lengths in O 2 − ͑H 2 O͒ is calculated to be 1.702 Å. 26 The shorter bond length in hydrated superoxide compared to O 4 − reflects the relative magnitudes of the binding energies for the two clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals form in biological reactions in living cells [1], but some external factors such as radiation, pollutants, physical stress, pesticides, several treatments etc. also cause its formation [2]. The highly reactive free radicals can initiate chain reactions interacting with proteins, lipids and DNA, and thereby damage the tissues [3].…”
Section: Introductionmentioning
confidence: 99%